(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The emergence of the English novel in the eighteenth century represented a major shift in literature, moving away from poetry and drama toward prose fiction that examined personal experience and social conditions. This paper explores the foundational contributions of Daniel Defoe, Samuel Richardson, and Henry Fielding, whose works helped shape the modern novel. Defoe’s stories, such as Robinson Crusoe, introduced realistic narrative techniques and psychological depth, focusing on survival, morality, and individual initiative. Richardson’s epistolary novels, including Pamela and Clarissa, emphasized emotional complexity and ethical challenges, offering insight into the characters’ inner lives. Fielding, through works like Tom Jones, combined satire, intricate plotting, and social observation, creating layered narratives that reflected the wider society. Collectively, these authors established key narrative methods and thematic concerns that influenced the development of the English novel and guided later writers. This study examines their unique approaches and the ways in which their innovations contributed to the evolution of the novel as a central literary form.